DETERMINANTS OF PRODUCTIVITY OF RESTAURANT AND DINING MSMEs IN SOUTH KUTA DISTRICT, BADUNG REGENCY - Ni Wayan Nia Lestari Sukantiasih; Putu Ayu Pramitha Purwanti (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
South  Kuta  District  is  a  strategic  area  with  significant  potential  for the   development   of   MSMEs,   particularly   in   the   culinary   sector   such   as restaurants and eateries that support local tourism. However, the productivity of MSMEs in this area still faces several challenges, including limited access to capital, low utilization of information technology, lack of financial literacy, and suboptimal  financial  inclusion.  This  study  aims  to  analyze  the  influence  of business   capital,   information   technology,   financial   literacy,   and   financial inclusion  on  the  productivity  of  restaurant  and  eatery  MSMEs  in  South  Kuta District,  Badung  Regency,  both  simultaneously  and  partially.  This  research adopts  a quantitative  approach  using  the  stratified  random  sampling method based on village and sub-district areas, with a total sample of 100 respondents. The data analysis technique employed is multiple linear regression. The results showthat  simultaneously,  the  four  independent  variables  have  a  significant influence  on  MSME  productivity.  Partially,  each  variable  also  demonstrates  a positive  and  significant  effect  on  productivity.  These  findings  indicate  that improving  access  to  capital, mastery  of  technology,  financial  management literacy,  and  the  expansion  of  financial  services  are  crucial  to  enhance  the productivity    and    competitiveness    of    MSMEs    in    the    tourism    sector. Collaboration among government agencies, financial institutions, and business actors is essential to achieve sustainable and inclusive MSME growth.